2014
DOI: 10.3184/095422914x14042081874564
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of soil quality and pollution assessment of heavy metals in cultivated soils of Henan Province, China

Abstract: Eight chemical and physical characteristics and seven biological properties of the soils from five cultivated areas in the Henan Province were quantified. Concentrations of Cu, Cr, Zn and Mn were determined using the flame atomic absorption spectrometry. In addition available phosphorus, chloride, soluble salt and pH were measured. The activities of enzymes were determined by a literature method. The results showed that the concentrations of Mn, Zn and Cr had close relationships with that of available phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Among these three locations, K content is lower in Hebei soil, [34] and the levels of Zn and Mn are higher in Henan soil. [35] Higher P levels were found in Shandong soil. [36] The corresponding contents of these elements were detected in foxtail millet samples from the corresponding locations.…”
Section: Principle Component Analysis and Discriminant Analysismentioning
confidence: 99%
“…Among these three locations, K content is lower in Hebei soil, [34] and the levels of Zn and Mn are higher in Henan soil. [35] Higher P levels were found in Shandong soil. [36] The corresponding contents of these elements were detected in foxtail millet samples from the corresponding locations.…”
Section: Principle Component Analysis and Discriminant Analysismentioning
confidence: 99%
“…Factor 3 was dominated by P, Cu, and Zn levels (45.40%, 73.64%, and 58.85%, respectively). Studies have shown that large quantities of Cu and Zn can be introduced to agricultural soil upon the application of phosphate fertilizer 52,53 . Additionally, the utilization of livestock manures and pesticides has also contributed to Cu and Zn levels in agricultural soil 54 .…”
Section: Correlation Analysis Resultsmentioning
confidence: 99%
“…The hotspots of APCS2, PMF-F2, Cu and Zn coincided with the spatial distribution of agricultural land types including grain crop land, orchard land and vegetable land. Agricultural chemical fertilizers are an important source of Cu and Zn enrichment, and phosphorus fertilizer is present in the highest amount in all inorganic fertilizers [ 49 52 ]. Cu and Zn are often used as additives in livestock diets to control scours [ 53 ].The amount of fertilizer applied to vegetable land is 5–10 times higher than that applied to other cultivated land [ 54 ].…”
Section: Discussionmentioning
confidence: 99%